The Problem of Property Rights to Land Acquisition of State (Jurisprudence and Conditions in Land National Law) - Mahli Ismail (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to answer the problem of construct and control of the state land by various parties to acquire the property. Structurally scholars of jurisprudence establishof three procedures, such as identification, turn and obtain approval from the government to acquire the property. While the provisions of the National Agrarian Land Legislation of Indonesia set-up of property rights happen in three ways; the determination of the government, the provision of conversion  and based on customary law. These requirements include the identification of former state land and wastelands and conditions, cultivation way, and obtaining permission from the government. While distinctive occur in terms designation and use of land in the Treasury Office into the absolute requirement for bookkeeping administrative enforcement of land rights. While the jurisprudence is not required certain types of plants or buildings in the enforcement of land rights administration books. While in general terms there should be plants and buildings as well as the limits of the fence is needed as a requirement in jurisprudence. While at the acreage requirement in the Treasury Office required two hectares per household, is an important requirement for the Treasury Office, because they want to regulate the distribution and people's livelihood of farmers` equalization.